THE INTERSECTIONALITY OF PROJECT-BASED LEARNING, SOCIOECONOMIC STATUS, AND ACADEMIC ACHIEVEMENT: A MULTIFACETED ANALYSIS - Trubus Semiaji; Sri Rahayu Pudjiastuti; Abdurohim (CV. ADIBA AISHA AMIRA, 2023)
This study explored the intersectionality of project-based learning (PBL), socioeconomic status (SES), and academic achievement through a multifaceted analysis. Quantitative analysis examined correlations between PBL implementation, SES indicators, and academic outcomes, revealing a positive association between PBL and improved achievement, particularly among students from lower SES backgrounds. Qualitative insights enriched understanding by highlighting challenges and opportunities of PBL across diverse socioeconomic contexts, emphasizing the role of family background and community support. Integration of quantitative and qualitative findings underscored the complex interplay between PBL, SES, and academic success, revealing convergent patterns and divergent perspectives. Implications for educational policy and practice were discussed, emphasizing the need for targeted interventions to address systemic inequalities and promote equitable access to quality education. Future research directions were also identified to further elucidate the dynamics of PBL, SES, and academic achievement. Overall, this study contributes to advancing knowledge on educational equity and student success, highlighting the potential of PBL as a tool for fostering inclusive learning environments.